The superior peer improves me: Evidence from swimming data - Shoko Yamane; Ryohei Hayashi (Osaka University, Institute of Social and Economic Research (ISER), 2018)
This study examined the peer effects of newcomer on the performance of existing members of teams, based on comparing the performances of swimming team members before and after the arrival of a newcomer. The identification strategy was similar to a natural experimental setting. This study found that the performance of an existing member of a team improves when a newcomer joins the team and that this effect is larger when the newcomer is a superior to the original team members.
Keywords: D62; L83; 330; Peer effect; Sports data